Why a Faith Community Nurse Program? A Five-Finger Response. Issue 2 (April 2015) - Ziebarth, Deborah Jean
<x xml:space="preserve">Abstract</x> ABSTRACT: The value of a faith community nurse (FCN) program is difficult to communicate in a concise and effective manner to hospitals. It is important for FCNs and FCN Coordinators to have a well-rehearsed, value-added response to the question, "Why a Faith Community Nurse Program?" This article presents a concise, evidence-based response to this question and demonstrates the value of a hospital-supported FCN program in a five-finger response illustration. A concise "elevator speech" is an important strategy to provide a quick response in scheduled, intended, opportunistic, or spontaneous informal interactions in hospitals, and impact stakeholder perception of FCN program value.